2009
DOI: 10.1590/s1413-85572009000200010
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de Burnout: um estudo comparativo entre professores das redes pública estadual e particular

Abstract: ResumoO objetivo deste estudo foi analisar se professores da rede pública estadual e professores da rede particular possuem diferentes dimensões de burnout (exaustão emocional, despersonalização e realização profissional), como também procurou verificar se variáveis demográficas, profissionais e laborais associam-se às dimensões de burnout de forma diferenciada nesses dois grupos. A amostra, do tipo conveniência, foi composta por 40 professores do ensino médio e fundamental, 20 da rede pública estadual e 20 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
0
5
0
5
Order By: Relevance
“…As a result, 35 studies were assessed for eligibility. After a full text analysis, 16 studies were additionally excluded, and 19 studies were included in the systematic review [ 2 , 4 , 13 , 14 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, 35 studies were assessed for eligibility. After a full text analysis, 16 studies were additionally excluded, and 19 studies were included in the systematic review [ 2 , 4 , 13 , 14 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main outcomes, sample size, and characteristics of the teachers of the included studies are shown in Table 1 . From the 19 articles included, 7 studies assessed burnout through the complete version of the Maslach Burnout Inventory (MBI) [ 2 , 22 , 23 , 26 , 30 , 34 , 35 ], 5 studies used the MBI Educators Survey (MBI-ED) [ 4 , 13 , 28 , 32 , 33 ], and 1 study implemented the MBI Human Services Survey (HSS) [ 31 ]. In addition, a further four tools were used to assess burnout syndrome in the teachers, with each questionnaire being implemented in one study as follows: Spanish Burnout Inventory, Education Professionals version (SBI-Ed) [ 21 ], Burnout Syndrome Inventory (BSI) [ 24 , 29 ], Burnout Syndrome Evaluation Questionnaire (CESQT) [ 14 , 25 ], and Burnout Teachers Questionnaire (BTQ-R) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference may be related to the large number of teachers from private schools in relation to the ones from public schools in both studies. Public school teachers are subjected to greater amount of stressors and they are more favorable to the emergence of psychopathological indicators, influencing on quality of life 34,35 . Interestingly, despite the high prevalence of musculoskeletal symptoms and stress, the basic school teachers evaluated in this survey were satisfied with the general quality of life (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…A atividade de docência é essencial para estruturação de uma sociedade e formação de seus indivíduos (LOPES, PONTES, 2009). Segundo Rubega, Pacheco (2000) e Santos (2013) esta profissão é responsável por -formar mão de obra e força de trabalho para a Sociedade Capitalista‖.…”
unclassified